The Effect of Socioeconomic Status on Well-being: A Systematic Literature Review - Nadhirah Binti Kamalulil, Errna; Aisyah Binti Panatik, Siti; Mohd Azam Wan Mohd Yunus, Wan (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims to systematically review articles on the relationship between socioeconomic status and well-being. In doing so, the present review identifies the various socioeconomic status components that may be linked to well-being. Guided by the PRISMA guideline, three electronic databases, Scopus, ScienceDirect, and Google Scholar, were employed. The articles were screened and selected based on the inclusion and exclusion criteria. A total of 15 articles were included in the review. The results of this review show that there is a significant influence between socioeconomic status and well-being among low-income groups. The findings also indicate that future study from various scholars should aim to focus on a broader context of socioeconomic status and well-being in order to fill the research gap found in the reviewed literature.